CULTURAL RESONANCE IN POPULIST COMMUNICATION: A COMPARATIVE STUDY OF POLITICAL RHETORIC ACROSS REGIONS - Abdul Rahman (Public Studies and Business Administration Journal (PUSBA), 2025)
This research examines the dynamics of global populism, which has transformed from mere economic articulation into a communication practice based on cultural identity through the mechanism of cultural resonance. Utilizing a narrative review approach that synthesizes literature from Scopus and Web of Science databases within the 2016-2026 period, this study analyzes how political actors build affective proximity through authenticity strategies and local symbolism. The findings indicate that while populism possesses a universal structure the dichotomy between "the people" and "the elite" its effectiveness relies heavily on cultural bricolage adaptive to regional contexts, such as nativism in Europe, anti-imperialism in Latin America, and religious morality in Asia. The theoretical integration of framing, social identity, and affective polarization reveals that this resonance is amplified by social media algorithms prioritizing emotional content, thereby deepening social segregation and the degradation of public discourse. The study concludes that addressing polarization requires systemic reforms in digital content distribution and media literacy approaches that move beyond cognitive fact-checking.